2014
DOI: 10.2147/opth.s54658
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and tolerability of dietary supplementation with a combination of omega-3 polyunsaturated fatty acids and antioxidants in the treatment of dry eye symptoms: results of a prospective study

Abstract: BackgroundWe assessed the effectiveness and tolerability of a dietary supplement based on the combination of omega-3 essential fatty acids and antioxidants on dry eye-related symptoms.MethodsA total of 905 patients (72% women, median age 60 years) with dry eye syndrome and using artificial tears to relieve symptoms participated in an open-label prospective intervention study. They were recruited during a routine ophthalmological appointment. Patients were instructed to take three capsules/day of the nutraceuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Despite the well-known disadvantages of an open-label design (eg, introduction of bias through unblinding), open-label trials are less complex and can be conducted at lower costs, and thus can be used to recruit more patients and to improve the value of results of clinical studies. In the present study, the open-label design was very useful to recruit a large number of patients diagnosed of glaucoma with dry eye symptoms in order to replicate the favorable results obtained in previous studies 21 , 22 using an oral omega-3 supplement in the patients with dry eye syndrome attended during routine daily practice. Some variables measured in the study may vary with the time of the day.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite the well-known disadvantages of an open-label design (eg, introduction of bias through unblinding), open-label trials are less complex and can be conducted at lower costs, and thus can be used to recruit more patients and to improve the value of results of clinical studies. In the present study, the open-label design was very useful to recruit a large number of patients diagnosed of glaucoma with dry eye symptoms in order to replicate the favorable results obtained in previous studies 21 , 22 using an oral omega-3 supplement in the patients with dry eye syndrome attended during routine daily practice. Some variables measured in the study may vary with the time of the day.…”
Section: Discussionmentioning
confidence: 93%
“… 18 On the other hand, inflammation and oxidative stress may play a key role in the development of dry eye syndrome. 13 , 19 , 20 Omega-3 polyunsaturated fatty acid supplementation has been shown to potentiate the antioxidant defenses, to relieve the bothering symptoms and signs of eye dryness by improving the lubrication and tear stability, and to reduce the ocular surface inflammation in patients with glaucoma, 21 in patients with pure dry eye, 22 24 in patients suffering from meibomian gland dysfunction, 25 , 26 and in patients after photoreactive keratectomy. 27 …”
Section: Introductionmentioning
confidence: 99%
“… 15 Three studies have previously shown symptomatic improvement in meibomian gland disease with oral omega-3 supplementation. 16 18 …”
mentioning
confidence: 99%
“…For instance, a mixture of four natural plant ethyl alcohol extracts decreased the levels of inflammatory cytokines and oxidative stress markers on the ocular surface in the murine dry eye model and antioxidant glasses containing extracts of medical plants which improved the OSDI score and TBUT in patients with dry eye disease [ 6 , 16 ]. In addition, omega-3 polyunsaturated fatty acids, such as antioxidants, have been found to be effective in improving dry eye symptoms [ 45 ]. Furthermore, Kim et al [ 46 ] reported that topical vitamin A eye drops contribute to improvements in blurred vision, TBUT, Schirmer's test, and findings from impression cytology in patients with dry eye disease.…”
Section: Discussionmentioning
confidence: 99%